RESEARCH OF EFFICIENCY OF FUNCTIONING TECHNICAL SYSTEM SPECIAL APPOINTMENTS ON THE BASIS OF MARKOVSKY PROCESS - N. A. Severtsev (Научный вестник МГТУ ГА)
The article deals with the complex system of a special purpose which is serviced by Markov's process. Two conditions for process of work of the researched system are given. The conclusion is made that all process of work of the researched system on servicing of the requests which have arrived after some timepoint does not depend on the process of our service before. The essential criteria for research of the system are listed. The criteria considering the economic factor of the system functioning are named. Separate types of servicing from the point of view of the researched system cost efficiency are determined. The cost efficiency of the system is determined, considering the losses from customers aircraft downtime, system operation expenses. Function of the cost of system losses with customers refusals in the process is determined. The author gives the formula for the criterion of the researched system cost efficiency as mass servicing system. The main requirements and formula dependences of service efficiency calculation of requests for the researched system are considered. Mathematical methods of calculation of the criteria considering economic efficiency of the researched system which characterize a degree of a given task performance course of operation are presented.